Response to Martin and Vanberg: Evaluating a Stochastic Model of Government Formation. (5th September 2014) - Golder, Matt; Golder, Sona N.; Siegel, David A.
<x content-type="archive" xml:space="preserve">Abstract</x> In a 2012 Journal of Politics article, we presented a zero-intelligence model of government formation. Our intent was to provide a "null" model of government formation, a baseline upon which other models could build. We made two claims regarding aggregate government formation outcomes: first, that our model produces aggregate results on the distributions of government types, cabinet portfolios, and bargaining delays in government formation that compare favorably to those in the real world; and second, that these aggregate distributions vary in theoretically intuitive ways as the model parameters change. In this issue, Martin and Vanberg (MV) criticize our model on theoretical and empirical grounds. Here we not only show how MV's evaluation of our model is flawed, but we also illustrate, using an analogy to common statistical practice, how one might properly attempt to falsify stochastic models such as ours at both the individual and the aggregate level.